2014
DOI: 10.5807/kjohn.2014.23.2.55
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organizational Justice, Empowerment on the Nursing Task Performance of Nurses: Focused on the Mediating Effect of Job Satisfaction and Organizational Commitment

Abstract: The purpose of this study is to analyze the structural model on the Nursing Task Performance of Hospital Nurses. Methods: Data collection was done by the 200 hospital nurses from May 1st to May 20th, 2013 in Seoul city. The sample variance-covariance matrix was analyzed using AMOS 19.0 and the maximum likelihood minimization function. The goodness of fit was evaluated using the SRMR, RMSEA and its 90% confidence interval, CFI, and TLI. Results: First, hospital nurses' organizational justice and empowerment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…However, in the group with low structural empowerment, nursing work outcomes were low, regardless of the level of bullying experience, supporting the direct effect between structural empowerment and nursing work outcomes. We found that structural empowerment had a significant direct association with nursing work outcomes, per previous research [ 39 , 40 , 41 ]. Nurses who are empowered at work perceive inter-professional collaboration and work more effectively [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, in the group with low structural empowerment, nursing work outcomes were low, regardless of the level of bullying experience, supporting the direct effect between structural empowerment and nursing work outcomes. We found that structural empowerment had a significant direct association with nursing work outcomes, per previous research [ 39 , 40 , 41 ]. Nurses who are empowered at work perceive inter-professional collaboration and work more effectively [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that for these nurses, the educational leadership of nursing unit managers is needed; education is essential to improve the competencies of staff nurses, and nursing unit managers must satisfy their education needs. When, staff nurses gain confidence through their education and communication, their job satisfaction and job commitment will increase, which will contribute to organizational performance [28].…”
Section: Discussionmentioning
confidence: 99%
“…The three concepts reflect the basic needs of the human being, consequently, they can be combined under the positive perception variable to meet those needs by the organization. Harrell-Cook et al (2017) indicated that organizations constantly seek to transform the positive perception of employees into positive attitude variables (Jun et al, 2014). Organizational commitment refers to the extent to which working individuals express their identity and feelings in accordance with the organization and the extent of loyalty to the organization (Allen et al, 2017;Mael & Ashforth, 1992).…”
Section: Positive-path Of Perception Attitude and Behaviormentioning
confidence: 99%
“…The perceived organizational justice variable is explained through the justice theory put forward by Adams (1965). The theory indicates that the cognitive evaluation of contributions (education, knowledge, and effort) is compared and measured with the gains that are obtained in return (Jun et al., 2014). On the basis cognitive assessment, workers judge the organization or its representatives as fair or not (Köse & Uzun, 2018).…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation